Sectors Using, Necessarity and Benefits of Green Technologies - Sodikjon Saidjonovich Mukhlisov (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses about the Green technologies, sectors using green technologies and the benefits of green technology and the obstacles to overcome